VALIDITY OF SOCIAL MEDIA VIDEO CONTENT AS A PROMOTIONAL MEDIA FOR SURABAYA'S CULINARY TOURISM CENTER (CASE STUDY: SUKOMANUNGGAL CULINARY TOURISM CENTER) - Fazriyana, Muhammad Fajar; Adriantantri, Emmalia; Myrtanti, Reiny Ditta; Sasmito, Agung Panji (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
Culinary tourism in Surabaya offers significant potential to support the regional economy, yet digital promotion remains underutilized. One example is the Sukomanunggal Culinary Tourism Center (SWK), which offers a variety of local specialties, yet its social media promotion remains minimal. This is despite current trends showing users preferring short, informative and engaging video content. This study aims to analyze social media video content as a promotional medium for the Sukomanunggal Culinary Tourism Center, focusing on the design, expert validation, and testing stages with the target audience. The method used was Research and Development (R&D) with the 4D model (Define, Design, Development, Disseminate). Instruments included observation, questionnaires, and an expert validation rubric. The results showed that a 60-second promotional video with a cinematic and storytelling approach effectively attracted audience attention, conveyed the uniqueness of local cuisine, and increased visitor interest. Expert validation stated that the video met technical, aesthetic, and promotional message effectiveness standards, while the audience response test yielded a feasibility score above 86%. The conclusion of this study proves that social media-based promotional video design is effective in increasing the visibility and attractiveness of SWK.